2012
DOI: 10.1038/eye.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

Using the real-life vision test to assess the functional vision of age-related cataract patients

Abstract: Purpose (1) To describe and validate a newly developed, timed performance-based measures of functional vision-the real-life vision test (RLVT). (2) To determine how RLVT relates to clinical measures and selfreport assessment of visual function and the complex interactions among visual impairment, psychosocial status, and demographic factors. Methods A total of 64 patients with age-related cataract and 45 age-matched controls were evaluated by four types of measurements: (1) demographic, medical, cognitive, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…In this test, Task 2 from the previous study 23 Reading and Chinese character picking in reduced illumination has been deleted from RLVT due to the less prevalence of reading in the darkness in real-life situations for elder people.…”
Section: The Real-life Vision Testmentioning
confidence: 99%
See 4 more Smart Citations
“…In this test, Task 2 from the previous study 23 Reading and Chinese character picking in reduced illumination has been deleted from RLVT due to the less prevalence of reading in the darkness in real-life situations for elder people.…”
Section: The Real-life Vision Testmentioning
confidence: 99%
“…Pioneering studies has demonstrated that PBMs can be reliable and valid methods in assessing real-life visual ability. [13][14][15][16][17][18][19][20][21][22][23] Owing to its significance in visual hierarchy, PBMs of visual function is becoming an important part of researches on the real-life effects of visual diseases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations